(untitled) (LEARNing Landscapes, 2021)
This article is a condensed version of the author’s research which explores the relationship between imaginative play and creativity in education, and examines the structures, approaches, benefits, and obstacles surrounding the topic of imaginative play and creativity. The photo collection is a reflection on the ponderings throughout the author’s project research. Inspired by zoom-in puzzles, a similar approach was taken to the creative representation of pedagogical wonderings through a photographic journey. By looking at things from different vantage points, one can see things in different ways, and, perhaps, experience a sort of catharsis through contemplation of the overlooked in the obvious.